2018
DOI: 10.4315/0362-028x.jfp-17-441
|View full text |Cite
|
Sign up to set email alerts
|

Observation of High School Students' Food Handling Behaviors: Do They Improve following a Food Safety Education Intervention?

Abstract: Youth are a key audience for food safety education. They often engage in risky food handling behaviors, prepare food for others, and have limited experience and knowledge of safe food handling practices. Our goal was to investigate the effectiveness of an existing food handler training program for improving safe food handling behaviors among high school students in Ontario, Canada. However, because no schools agreed to provide control groups, we evaluated whether behaviors changed following delivery of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Evaluation of an educational intervention with Canadian high school students found poor hand hygiene and use of temperature probes pre-intervention, and risky practices remained post-intervention [26], eliciting the need for reinforcement to build good food hygiene habits post-education. Habit strength can improve food safety behaviours, which can be strengthened by providing cues to action and reminders [27].…”
Section: Comparison To Other Researchmentioning
confidence: 99%
“…Evaluation of an educational intervention with Canadian high school students found poor hand hygiene and use of temperature probes pre-intervention, and risky practices remained post-intervention [26], eliciting the need for reinforcement to build good food hygiene habits post-education. Habit strength can improve food safety behaviours, which can be strengthened by providing cues to action and reminders [27].…”
Section: Comparison To Other Researchmentioning
confidence: 99%
“…Therefore, research is required to investigate the effectiveness of tailoring on hygienic food-handling behavior. Previous research on generic interventions found that, despite an increase in hygienic behaviors, participants continued to use risky practices after the intervention, suggesting that the transmission risk of foodborne diseases remained [ 18 ]. A tailored intervention targeting empirically assessed attributes of the recipients that are relevant to the outcome behavior is expected to yield more behavioral change than a generic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown significant effects on educational interventions by assessing other contexts such as food security (Diplock et al, ; Young et al, ), food waste (Romani, Grappi, Bagozzi, & Barone, ; Stöckli, Niklaus, & Dorn, ) and environmental behavior (Zelezny, ). Still, these researchers suggest that further research on educational intervention is needed.…”
Section: Discussionmentioning
confidence: 99%